Expert Examination of the Use of a Dependent Invention and a Dependent Utility Model Under the Law of the Russian Federation - Evgenievich Kitaiskiy, Vladimir; Nikolaevich Petrov, Evgeniy; Vladimirovna Shvedova, Vera (International Journal of Engineering and Technology, 2018)
The article deals with such objects of patent law as inventions and utility models, the use of which by patent holders in some cases is limited by the rights of other patent owners in accordance with the requirements of the Civil Code of the Russian Federation, as amended on March 12, 2014. Such inventions and utility models are called dependent. In fact, these are improvements to other inventions and utility models, to which the exclusive right applies. The patent owner of such a dependent object of patent law may legitimately use his invention or his utility model only upon obtaining the right to use another (main) object of patent law or at its alienation from the legal owner. For this, it is necessary to reveal the dependence of one's object of patent law on another (main) object. The article shows how it is possible to identify such dependence under the existing patent legislation of the Russian Federation.Â Â